IL-25–induced shifts in macrophage polarization promote development of beige fat and improve metabolic homeostasis in mice - Li, Lingyi; Ma, Lei; Zhao, Zewei; Luo, Shiya; Gong, Baoyong; Li, Jin; Feng, Juan; Zhang, Hui; Qi, Weiwei; Zhou, Ti; Yang, Xia; Gao, Guoquan; et al. (PLOS Biology, 2021)
Beige fat dissipates energy and functions as a defense against cold and obesity, but the mechanism for its development is unclear. This study reveals that IL-25 is upregulated upon cold exposure and induces beige fat formation, with corresponding benefits to metabolic homeostasis; the effects of IL-25 are mediated by changes in macrophage polarization, which in turn influence tissue innervation.